SUSTAINABLE KEY PERFORMANCE INDICATORS FOR URBAN REGENERATION PROJECTS - Aladag, Hande; Isik, Zeynep (YILDIZ TECHNICAL UNIV, 2016)
The construction industry needs to assess its success in the long term considering the internal and external parameters affecting its performance. Urban regeneration projects have a considerable importance in terms of construction industry. Efforts have been exerted to overcome the problem of increase in building supply in contrast to the decrease in building demand with urban regeneration projects which don't increase building supply, yet increase building demand. Besides, urban regeneration projects have the potential to be a driving force for the Turkish economy by manufacturing construction materials and in terms of engineering, technical consultancy and potential construction works. In order to provide an efficient performance for the Turkish construction industry in the long term, it is crucial to determine benchmarks and indicators, which affect the performance of urban regeneration projects. In this context, this study aims to investigate the Sustainable Key Performance Indicators (SKPIs) and their effects on success.
Keywords: Performance management; sustainable performance; urban regeneration; construction industry; CONSTRUCTION-INDUSTRY; CONTRACTOR SELECTION; Engineering